Sero-positivity and hematological markers of dengue fever in western Nepal - Dhakal, A; Rijal, B (Devdaha Medical Journal, 2025)
Introduction: Dengue fever is increasingly emerging as a public health threat in Nepal, progressively spreading from the terai plains into the hilly regions. This study evaluated the prevalence of dengue sero-positivity and related hematological changes among suspected cases in western Nepal. Methods: A prospective study was performed from June 2022 to May 2023, including 657 patients clinically suggestive of dengue. Diagnostic measures included rapid NS1 antigen tests and serological IgM/IgG assays, together with hematological parameters. Results: Out of 657 suspected individuals, 70 (10.5%) were confirmed dengue-positive. Specifically, 34.2% tested positive for NS1 antigen (n = 24), 68.5% for IgM antibodies (n = 48), and 12.8% for IgG antibodies (n = 9). 60% of the infections were among inpatients, with the age group 20–29 years most affected (28.5%), followed by 40–49 years (20%). A surge in cases was observed in November (42.9%). Hematologically, 27.1% had platelet counts below 150000/mm3 and 25.7% showed leucopenia (< 4000/mm3). Conclusion: Dengue sero-positivity among suspected cases in western Nepal was 10.5%, with recent infections (IgM positivity) predominating. The most affected age group was 20–29 years, and cases peaked in November. Thrombocytopenia and leucopenia were observed in over a quarter of confirmed cases, highlighting common hematological disturbances associated with dengue in this region.